Integrating Mbojo Folklore and Culture Preneurship to Shape Modern Leadership Values - Alaini, Nining Nur; Hidayatullah, Dede; Saefuddin, Saefuddin; Supriadi, Asep; Rohim, Rohim; Ali, Tengku Intan Marlina Tengku Mohd (Pandawan, 2025)
The Mbojo community in West Nusa Tenggara has a folklore entitled